2012
DOI: 10.1021/es300894r
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Contributions of Brake Dust, Tire Wear, and Resuspension to Nonexhaust Traffic Particles Derived from Atmospheric Measurements

Abstract: Size-fractionated samples of airborne particulate matter have been collected in a number of campaigns at Marylebone Road, London and simultaneously at background sites either in Regents Park or at North Kensington. Analysis of these samples has enabled size distributions of total mass and of a number of elements to be determined, and roadside increments attributable to nonexhaust emissions arising from traffic activity have been calculated. Taking a novel approach, the combined use of size distribution informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
301
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(334 citation statements)
references
References 31 publications
29
301
1
3
Order By: Relevance
“…The mode centered at around 2.6 µm (Street) essentially comprised coarse particles, and was mainly attributed to traffic sources following interpretation from previous research linking the coarse fraction to tyre wear, road abrasion, and re-suspended dust (Harrison et al, 2012;Lenschow et al, 2010;Ondráček et al, 2011;Pant and Harrison, 2013;Thorpe and Harrison, 2008). The relative abundance of such particles in the lower part of tree crown depicts the availability of their source at the ground level, which could be either through direct emission or particle resuspension.…”
Section: Discussionmentioning
confidence: 71%
“…The mode centered at around 2.6 µm (Street) essentially comprised coarse particles, and was mainly attributed to traffic sources following interpretation from previous research linking the coarse fraction to tyre wear, road abrasion, and re-suspended dust (Harrison et al, 2012;Lenschow et al, 2010;Ondráček et al, 2011;Pant and Harrison, 2013;Thorpe and Harrison, 2008). The relative abundance of such particles in the lower part of tree crown depicts the availability of their source at the ground level, which could be either through direct emission or particle resuspension.…”
Section: Discussionmentioning
confidence: 71%
“…Non-exhaust particulate emission factors were adjusted based on work by Harrison et al (2012), who analysed measurements of speciated and size-segregated particulates at the Marylebone Road monitoring site and nearby urban background sites, made during four month-long campaigns between 2007 and 2011. Non-exhaust emissions were found to contribute 77 % of the total traffic-related particulate emissions, with 55 % of the non-exhaust attributable to brake wear and smaller proportions from resuspension of road dust and tyre wear.…”
Section: Road Traffic Emissions Factor Adjustmentsmentioning
confidence: 99%
“…Lin et al, 2005;Ntziachristos et al, 2007), and non-tailpipe emissions caused by abrasion of brakes (e.g. Councell et al, 2004;Lough et al, 2005;Schauer et al, 2006;Johansson et al, 2009;Pérez et al, 2010;Apeagyei et al, 2011;Song and Gao, 2011;Harrison et al, 2012). Dall'Osto et al (2013), for example, found a comparable brake dust factor characterized by Cu and Fe with a strong 30 diurnal pattern.…”
Section: Primary Vehicle Emissionsmentioning
confidence: 99%